PEOPLE MANAGEMENT IN THE AGE OF ARTIFICIAL INTELLIGENCE AND AUTOMATION (REMUNOM, 2025)
Technological evolution has brought profound changes to labor relations and business management models. The rise of Artificial Intelligence (AI) and automation has transformed not only operational processes but also the roles performed by professionals within organizations. The replacement of repetitive tasks with intelligent machines and automated algorithms requires leaders to be more strategic, inclusive, and prepared to handle the new demands of an increasingly digital and dynamic labor market. In this context, the present scientific article aims to discuss people management in the era of Artificial Intelligence (AI) and automation. Therefore, the general objective is to understand the effects of Artificial Intelligence and automation on people management. The choice of this topic is justified by the current relevance of the debate on the future of work and the need to promote critical reflection on how organizations are adapting to the new technological reality. Regarding the methodology, this research is characterized as qualitative, exploratory in nature, with a descriptive focus. The approach method adopted is deductive, based on a bibliographic review. In the end, it was possible to conclude that the key to success in the age of Artificial Intelligence and automation lies in a more conscious, strategic, and human-centered people management.